New dynamics in old age: individual, environmental, and societal perspectives - Wahl, Hans-Werner; Tesch-Römer, Clemens; Hoff, Andreas (Taylor and Francis, 2006)
Cover -- Title Page -- Copyright Page -- Table of Contents -- Preface: On New Person-Environment Dynamics in Old Age: Opportunities and Constraints -- PART I: INTRODUCTION -- 1. Searching for the New Dynamics in Old Age-A Book Opener -- OLD AGE UNDER TRANSFORMATION -- LACK OF CONSIDERATION OF THE "OLD" AND "NEW" DYNAMICS OF OLD AGE -- ON THE DYNAMICS OF OLD AND NEW AGING: ATTEMPT TO DEFINE A FUZZY CONCEPT -- The Emergence of the Fourth Age -- The Scientific Management and Biomedicalization of Old Age -- Changing Dynamics in the Gerontological Imagination -- New Societal Discourses about Aging -- APPROACHING THE NEW AGING: CONCEPT OF THE BOOK -- REFERENCES -- 2. The Social Construction of Age and the Experience of Aging in the Late Twentieth Century -- THE INVENTION AND USES OF CHRONOLOGICAL AGE -- Calendars, Timelines, and Chronology -- WHY IS IT IMPORTANT TO KNOW YOUR AGE? -- Childhood and Adolescence -- Adulthood and Full Citizenship -- Postadult or Old Age -- AGE STRUCTURES AND AGE STRATIFICATION -- AGE WITHOUT CHRONOLOGY -- Generational Life Courses -- Age-Classed Life Courses -- AGE WITH CHRONOLOGY -- Age Statuses and Staged Life Courses -- Age Stratification and the Experiences of Growing Older -- Education -- Marriage and Family -- Policies of the State -- THE EXPERIENCE OF OLD AGE -- The Invention of Old Age -- Time and the Ageless Self -- REFERENCES -- 3. Changes in Physical and Mental Function of Older People: Looking Back and Looking Ahead -- THE NEW HEALTHY ELDERLY: ONLY GETTING BETTER -- DATA AND METHODS -- RESULTS -- Population Counts -- Age Standardized Rates and Counts -- DISCUSSION AND CONCLUSIONS -- REFERENCES -- PART II: NEW AND PERSISTENT DYNAMICS REGARDING THE SOCIAL ENVIRONMENT -- 4. Cohort Differences in Social Relations among the Elderly -- CURRENT AND PAST THEORIES OF SOCIAL RELATIONS
Keywords: Aufsatzsammlung; Soziale Situation; Gerontologie; Alter; Alterssoziologie